2019
DOI: 10.1038/s41598-019-48406-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Long-term Fertilization on the Molecular Structure of Humic Acid and Organic Carbon Content in Soil Aggregates in Black Soil

Abstract: Soil aggregates are the basic units of soil structure, and their composition and carbon (C) stability directly affect soil fertility. As cementing agents, humic substances play an important role in the formation and stability of soil aggregates. Long-term fertilization not only changes the structure of humic acid (HA), but also affects the content and stability of organic C in soil aggregates. In this study, based on a long-term fertilization experiment, the relationship between the molecular structure of HA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The results showed that an absorbance peak at 1217,1370, 1741 cm -1 for cellulose and the 1258, 1365, 1737cm -1 for nanocellulose was observed. Both cellulose and nanocellulose absorbance peaks at 1217 and 1216cm Similar result was obtained by [14,15] reported that the absorbance peak at 1050 cm -1 is due to C-O Stretching, the peaks at 1730,1720 cm -1 are assigned to the C=O stretching indicates the microcrystalline cellulose. [16] also reports the C-O stretching to confirm the presence of cellulose.…”
Section: Fourier Transform Infrared Spectrometer (Ftir)supporting
confidence: 81%
“…The results showed that an absorbance peak at 1217,1370, 1741 cm -1 for cellulose and the 1258, 1365, 1737cm -1 for nanocellulose was observed. Both cellulose and nanocellulose absorbance peaks at 1217 and 1216cm Similar result was obtained by [14,15] reported that the absorbance peak at 1050 cm -1 is due to C-O Stretching, the peaks at 1730,1720 cm -1 are assigned to the C=O stretching indicates the microcrystalline cellulose. [16] also reports the C-O stretching to confirm the presence of cellulose.…”
Section: Fourier Transform Infrared Spectrometer (Ftir)supporting
confidence: 81%
“…The ratio of aliphatic C/aromatic C can reflect the complexity of the molecular structure of humic substances. A higher ratio indicates a lower content of aromatic core structures in humic substances, more aliphatic side chains, a lower degree of condensation, and a simpler molecular structure 8 . The results of this study demonstrated that the ratio of aliphatic C/aromatic C of the soil organic carbon in the full rotary tillage return treatment was higher than in the other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Soil HMC accounts for the largest proportion of SOC (Dou et al, 2020). Traditional organic materials have the capacity to improve the formation of soil humic substances (Yang et al, 2019;Jiuming Zhang et al, 2019). Biochar as a kind of organic amendment has received little attention in previous studies.…”
Section: Effects Of Straw and Straw-derived Biochar On Soil Organic C...mentioning
confidence: 99%